In vitro and in vivo comparison of different grades of chitosan with common surgical hemostats - Sasidaran, Ramesh (2011)
The most common cause of significant intra-operative bleeding is inadequate surgical hemostasis. Nearly all reviews of intra-operative and early post-operative bleeding point that 75% to 90% of all bleeding is technical in nature. Whatever the cause, uncontrolled bleeding can lead to a combination of factors which may further exacerbate the problem of a vicious bloody circle. Dilutional thrombocytopenia, platelet dysfunction and consumption of clotting factors present a difficult problem to address as continual blood loss continue to compound the problem while blood component replacement therapy attempts to correct the deficiency. Our study aims to compare haemostatic efficacy of different grades of chitosan compared to the common haemostatic surgical hemostats. We hypothesize that chitosan based hemostats are superior to the common surgical hemostats in inducing platelet aggregation, affecting Prothrombin Time and Partial Thromboplastin Time and red cell aggregation. There were two parts to the study. In the in vitro study blood sample was obtained from the blood bank. Blood sample was collected utilizing the CP2D/AS-3 systems with additive solution (AS-3,Nutricel® ) to maintain red blood cell viability. Collected whole blood was separated into four separate components ( whole blood, heparinized whole blood, platelet rich and platelet poor plasma) . In the platelet aggregation test, stirred citrated PRP was contacted with 3.5 mg of each haemostatic agent premoistened with 100 micro liter of phosphate-buffered saline (PBS) in a test tube (as would be used in traditional platelet aggregometry). Aliquots of supernatant (100 micro liter) were removed every 5 minute for a total of 15 minutes and the platelet count was measured in triplicate utilizing an electronic cell counter (XT2000i Sysmax Analyzer, Sysmex America Inc., Mundelein, Illinois); platelet counts from each experimental aliquot were normalized using counts from unreacted PRP. For each haemostatic agent three independent sets of experiments were performed. A similar set of platelet aggregation experiments was performed using the haemostatic sponge agents ( 3 Different grades of Chitosan, Lyostypt® , and Surgicel®) premoistened with PBS. In the PT/PTT test, each haemostatic agent was reacted with platelet rich and platelet poor plasma. The serum was centrifuged to remove possible deposition. Six parallel experiments were conducted to measure PT and APTT of the serum using a hemostasis analyzer (Stago STA Compact Haemostatic Analyzer, Diamond Diagnostics, MA. USA) In the red cell aggregation test, each haemostatic agent was reacted with whole blood, heparinized blood and platelet poor blood. The blood with haemostatic agents were left to stand and the erythrocyte sedimentation rate was measured with the Sedy400 sedimentation analyzer. In the animal experiment, 36 Sprague-Dawley rats were utilized. Under general anesthesia, via a midline laparotomy the right and left kidneys were isolated. Heminephrectomies were carried out and hemostats were applied to the cut surface and time taken to hemostasis was tabulated. In the platelet aggregation test, no definite trend in platelet aggregation was observed. No CMC 36 3% showed the lowest platelet count of all haemostatic agents at 5 minutes. Lyostypt® and Surgicel® were superior compared to chitosan hemostats at 10 minutes of contact. In the coagulation test (PT/PTT ) mean prothrombin time for Chitosan (NoCMC 8%) was the shortest in platelet rich plasma. Mean partial thromboplastin time was the shortest for Chitosan (NoCMC 3%) in platelet rich plasma. In platelet poor plasma, the shortest prothrombin time was seen in both the Chitosan hemostats( NoCMC 3% and NoCMC8%). Partial thromboplastin time was shortest for Chitosan (NoCMC 3%) hemostat. In the red cell aggregation test, Chitosan hemostat(NoCMC 3%) demonstrated the highest erythrocyte sedimentation ratio in platelet poor blood as well as heparinized blood specimens. Chitosan hemostat (NoCMC 8%) demonstrated the highest erythrocyte sedimentation ratio in heparinized whole blood. In the animal experiment, there was no statistical difference between the hemostats in arresting bleeding from heminephrectomy specimens. The Chitosan hemostat(NoCMC 36 3%) however demonstrated the shortest time to hemostasis compared to the otherhemostats. From the study we concluded that Chitosan hemostats causes platelet to aggregate the earliest compared to other hemostats. They shorten prothrombin and partial thromboplastin time. They have been also found to aggregate red blood cells the most compared to other haemostatic agents.